Crystal structure of (E)-4-{4-[ethyl(2-hydroxyethyl)amino]styryl}-1-methylpyridinium nitrate hemihydrate - Hui Zhang; Mu-Hua Peng; Xiao-Juan Wang; Xiao-Ying Li (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The asymmetric unit of the title compound, C18H23N2O+·NO3−·0.5H2O, contains two independent 4-{4-[ethyl(2-hydroxyethyl)amino]styryl}-1-methylpyridin-1-ium cations, two nitrate anions and one lattice water molecule. In the cations, the pyridine ring is twisted with respect by 7.98 (12) and 18.42 (10)° to the benzene ring. In the crystal, the cations, the anions and the lattice water molecules are linked by O—H...O hydrogen bonds and weak C—H...O hydrogen bonds, forming a three-dimensional supramolecular architecture. π–π stacking occurs between pyridine and benzene rings of adjacent cations, the centroid–centroid distances being 3.8169 (15) and 3.8663 (14) Å. In the crystal, one of the independent cations is disordered, the central vinyl unit and the terminal hydroxylethyl group being disordered over two sets of sites with site occupancy factors of 0.600 (6) and 0.400 (6).